MYB Transcription Factors as Regulators of Secondary Metabolism in Plants - Cao, Yunpeng; Li, Kui; Li, Yanli; Zhao, Xiaopei; Wang, Lihu (Biology (Basel, Switzerland), 2020)
MYB transcription factors (TFs), as one of the largest gene families in plants, play important roles in multiple biological processes, such as plant growth and development, cell morphology and pattern building, physiological activity metabolism, primary and secondary metabolic reactions, and responses to environmental stresses. The function of MYB TFs in crops has been widely studied, but few studies have been done on medicinal plants. In this review, we summarized the MYB TFs that play important roles in secondary metabolism and emphasized the possible mechanisms underlying how MYB TFs are regulated at the protein, posttranscriptional, and transcriptional levels, as well as how they regulate the downstream target gene networks related to secondary metabolism in plants, especially in medicinal plants.